Kemandirian Belajar Fisika pada Peserta Didik dengan Pembelajaran Berbasis Proyek - Puspitasari, Reni Dwi; Latifah, Sri; Wati, Widya; Yana, Elsy Tri (Indonesian Journal of Science and Mathematics Education, 2018)
Abstarct:This study aims to 1) Know the effects of project-based learning on the independence of physics learning, 2) To know how much influence of project-based learning on the independence of physics learning. The type of research used is Quasi Eksperimen method using experiment and control group. The population of this study were all students of class X, Samples taken with Simple Random Sampling technique, students of class X Tkj1 as control class and class X Tkj2 as experimental class. data collection instruments used in the form of tests, questionnaires, observations and documentation. The results of research are; 1) The effect of project-based learning on the independence of learners, 2) The magnitude of the influence of project-based learning on the independence of learning based on the analysis of the independence test questionnaire data in the experimental class with the average total of 76% and the control class the average total number of 60% including the moderate category. test Hypothesis of control class and experimental class calculation result of tcount 2,357 and ttabel 1,697, it can be concluded that the influence of self-reliance learning physics on learners SMK N 7 by using project-based learning. After this learning is expected learners more easily understand the material and can create new business field.  Abstrak: Penelitian ini bertujuan untuk 1), Mengetahui pengaruh pembelajaran  berbasis proyek terhadap kemandirian belajar fisika,2) Mengetahui seberapa besar pengaruh pembelajaran berbasis proyek terhadap kemandirian belajar fisika. Jenis penelitian yang digunakan adalah metode  Quasi Eksperimen dengan menggunakan kelompok eksperimen dan kontrol. Populasi  penelitian ini adalah seluruh peserta didik kelas X, Sampel yang di ambil  dengan teknik Simple Random Sampling, peserta didik kelas X Tkj1  sebagai kelas kontrol dan kelas X Tkj2 sebagai kelas eksperimen. instrumen pengumpulan data yang digunakan berupa tes,  angket, observasi dan dokumentasi. Hasil penelitian  adalah; 1) Adanya pengaruh pembelajaran berbasis proyek terhadap kemandirian peserta didik, 2) Besar pengaruh pembelajaran berbasis proyek terhadap kemandirian belajar berdasarkan analisis data nilai angket kemandirian pada kelas eksperimen dengan jumlah total rata-rata 76% dan pada kelas kontrol jumlah total rata-rata 60% termasuk kategori sedang. uji Hipotesis  hasil perhitungan kelas kontrol dan kelas eksperimen sebesar  thitung  2,357 dan ttabel 1,697, dapat disimpulkan bahwa adanya pengaruh kemandirian belajar fisika pada peserta didik SMK N 7 dengan menggunakan pembelajaran berbasis proyek. Setelah pembelajaran ini diharapkan peserta didik lebih mudah  memahami materi dan dapat menciptakan lapangan usaha baru.